UPAYA MENINGKATKAN KEMAMPUAN MENYUSUN KARYA ILMIAH MELALUI METODE DIRECT INSTRUCTION DALAM IN HOUSE TRAINING PADA GURU DI SD NEGERI 1 TUKSONGO - Elisyani, Nurma (Information Technology Education Department, 2023)
Facts on the ground, regarding teachers' motivation and interest in compiling scientific work are still far from expectations. The phenomenon that occurred at SD Negeri Tuksongo 1, which is a school where the researcher served as the principal, showed that the teacher's ability to compose scientific work was still lacking. Based on the results of initial observations conducted by researchers through supervision, out of 8 teachers only 3 teachers had the ability to compose excellent scientific work. In addition, teachers are reluctant to take part in various scientific activities held by the education office or other institutions, on the grounds that teachers feel inconvenienced related to the preparation of scientific work. by carrying out Direct Instruction activities in In House Training (IHT). The aims of this study are the first describes the implementation of the Direct Instruction in House Training method in increasing the ability to compose scientific work for teachers at SD Negeri Tuksongo 1. The second describes the ability level for compiling scientific work for teachers at SD Negeri Tuksongo 1 after implementing the Direct Instruction In method House Training. The subjects in this study were 8 teachers at SD Negeri Tuksongo 1, Borobudur District, Magelang Regency, consisting of 5 civil servant teachers and 3 first aid teachers. The results of the implementation of the action are the average score of scientific work assessment in cycle 1 the average score is 17 (in the good category), in the second cycle the average score is 20.5 (in the very good category). Based on the results of this study, Direct Instruction in House Training can improve the ability to prepare teachers' scientific work.